Effect of Steroid Hormone (Ecdysone) on the Pupal and Larval Developments of Tribolium castaneum (Herbst) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Ecdysone is a steroid hormone especially found in insects and mammals. One day old pupae of Tribolium castaneum were exposed to crude ecdysone at different concentrations of 10, 20, 40, 80, 160, and 320 μl/kg of whole wheat flour each for 1, 3 and 5 days. Adult recovery was significantly reduced in the treated pupae (F=3.47, P